Making Virtual Global Learning Transformative and Inclusive: A Critical Reflective Study on High-Impact Practices in Higher Education - Guo-Brennan, Linyuan (Journal of Teaching and Learning, 2022)
The COVID-19 pandemic has highlighted the importance of global competence, agility, empathy, and innovation in managing opportunities, crises, and problems. Global learning and engagement in higher education is the pathway towards developing learners' intercultural competence, fostering an appreciation of diversity, inclusion, and equity, and empowering individual agency towards collective wellbeing and sustainability. Digital transformation and available tools have expanded the scope and depth of global learning in virtual environments. This article reports a critical reflective study on virtual global learning and shares high-impact, evidenced-based strategies to make virtual global learning more equitable, inclusive, meaningful, and relevant to all learners in higher education.